PENGEMBANGAN TES BAHASA INGGRIS KOMUNIKATIF UNTUK SMK PARIWISATA DI BALI - I Nengah Astawa; Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
This research was conducted at SMK in Bali which aims to develop a model of communicative English test for SMK Tourism in Bali by involving students of English Education Study Program as the final project of language tesing. This research is conducted for two years using Research and Development method so that the developed product can be believed to be correct and accurate. The research was conducted because the crucial important problem faced by SMK Tourism teachers in assessing the ability of communicative English students so that teachers and students know their true ability in English communication in order to improve the quality of learning so that students will be ready to work in various tourism industries. In the first year, research was focused on establishing a communicative English test model based on analyzing an English test that already exists at SMK Tourism in Bali and then designing a model of Communicative English test for vocational students in Bali.